Combinatorial synthesis of soluble conjugated polymeric nanoparticles and tunable multicolour fluorescence sensing. Issue 37 (31st August 2017) - Zhao, Peng; Dai, Yanan; Wu, Yusen; Wang, Lili; Huang, Binlei; Ding, Yun; Hu, Aiguo
Abstract : Combinatorial polymerization method has been exploited to prepare a library of soluble conjugated polymeric nanoparticles (SCPNs), by varying symmetrical monomers, A x and B y ( x > 2, y ≥ 2), plus modification with variant terminal groups. Abstract : A combinatorial polymerization method has been exploited to prepare a library of soluble conjugated polymeric nanoparticles (SCPNs) through palladium catalyzed polycondensations in confined nanoreactors. The strategy of independent variation within two complementary families of simple and symmetrical monomers, A x and B y ( x > 2, y ≥ 2), plus post-polymerization modification with variant terminal groups greatly increases the number of polymers and improves the efficiency of polymer preparation. Fluorescence properties (band gap) of the SCPNs are easily tuned by selecting the monomer units (A or B) and the terminal (T) substituents through this "TABulated synthesis" method, providing fluorescent polymers that cover the whole visible spectrum, from blue to red. This library of SCPNs is further utilized for multicolor fluorescence sensing of explosives, showing a high Stern–Volmer quenching constant ( K sv ). Meanwhile, the K sv values of the SCPNs were mapped with the variation of the T, A, and B building blocks to predict the possible SCPN member with the optimal K sv value ( K sv up to 1.2 × 10 5 M −1 ), showing the academic significance of this method. We believe that such a combinatorial "TAB" strategy provides a straightforward method to quickly synthesize libraries of polymeric nanoparticles, which will promote widespread studies on the functional materials in interdisciplinary fields.